The Effectiveness of Acupuncture for Herpes Zoster: A Systematic Review and Meta-Analysis - Seong-Kyeong Choi; Jeong-Hyun Moon; Woo-Seok Jang; Jung-Eun Jang; Si-Hyun Park; Won-Suk Sung; Chan-Yung Jung; Byung-Kwan Seo; Seung-Deok Lee; Kyung-Ho Kim; Eun-Jung Kim (MEDrang Inc., 2023)
Herpes zoster (HZ) results from the reactivation of a varicella-zoster virus infection and is accompanied by moderate-to-severe pain in most patients. The most common treatment is medication; however, there are still limitations. Acupuncture reportedly has meaningful therapeutic effects and is a possible alternative option in HZ. However, no systematic reviews examining the use of acupuncture and electro-acupuncture (EA) alone have been published; in this study, we therefore aimed to systematically review those techniques. We searched for clinical trials of acupuncture and EA treatment for HZ up to October 2022. Trials that used acupuncture were included. Outcomes were visual analog scale (VAS) and effective rate. Secondary outcomes were time to pain relief, time to pain elimination, incrustation, decrustation, lastly incidence of post-herpetic neuralgia (PHN). In total, 22 randomized controlled trials were included in this research. Compared with conventional medication therapy, acupuncture was associated with a significant improvement in VAS, effective rate, and times to pain relief and elimination. Times to new blister cessation, incrustation, and decrustation (days) were significantly improved. Furthermore, the incidence rate of PHN was lower in acupuncture groups. The results suggest that acupuncture could be a reasonable treatment option for patients with HZ who suffer from pain and accompanying symptoms.